Concepts of Neuroinflammation and Their Relationship With Impaired Mitochondrial Functions in Bipolar Disorder - Cyrino, Luiz Arthur Rangel; Delwing-de Lima, Daniela; Ullmann, Oliver Matheus; Maia, Thayná Patachini (Frontiers in Behavioral Neuroscience, 2021)
Bipolar disorder (BD) is a chronic psychiatric disease characterized behaviorally by frequent episodes of depression and mania, and neurologically by dysregulated neurotransmission, neuroplasticity, growth factor signaling, and metabolism, as well as by chronic neuroinflammation, oxidative stress, and neuronal apoptosis. These abnormalities result from complex interactions between multiple susceptibility genes and environmental factors such as stress. The neurocellular abnormalities of BD can result in gross morphological changes, such as reduced prefrontal and hippocampal volume, and circuit reorganization resulting in cognitive and emotional deficits. The term “neuroprogression” is used to denote the progressive changes from early to late stages, as BD severity and loss of treatment response correlate with the number of past episodes. In addition to circuit and cellular abnormalities, BD is associated with dysfunctional mitochondria, leading to severe metabolic disruption in highly energy-demanding neurons and glia. Indeed, mitochondrial dysfunction involving electron transport chain disruption is considered the primary cause of chronic oxidative stress in BD. The ensuing damage to membrane lipids, proteins, and DNA further perpetuates oxidative stress and neuroinflammation, creating a perpetuating pathogenic cycle. A deeper understanding of BD pathophysiology and identification of associated biomarkers are needed to facilitate early diagnosis and treatment of this debilitating disorder.